A preventive cytokine treatment of the viral infectious bursal disease (IBD) of chickens - Mattiello, Rosana (2015)
Infectious bursal disease (IBD) is a viral disease of young chickens that produce severe lesions in the bursa of Fabricius and other organs inducing immunosuppression and mortality in birds. This study indicates that oral administration of IFN-α and IL-2 during 16 days produced a significant reduction in animals’ morbidity and mortality to IBD virus (IBDV) infection accompanied with a decrease in symptoms and bursal tissue damage. The treatment also increased body weight, not only in birds challenged with IBDV, but also in uninfected controls. Infected birds treated with cytokines presented the same bursal index and organs’ weight that controls; since untreated animals showed a significant decrease in these parameters. Finally, cytokine administration represents a new alternative to IBDV vaccination.